Coercive Diplomacy Recalibrated: Evaluating Effectiveness, Risks, and Modern Challenges - Hind MOUSLIM (African Scientific Journal, 2025)
Abstract Coercive diplomacy, the strategic use of threats or limited force to compel an adversary, remains a persistent instrument in international relations despite its contentious history and uncertain outcomes. This article argues for a necessary "recalibration" of our understanding and application of this tool, critically evaluating its effectiveness, inherent risks, and viability amidst the complexities of the 21st century. It addresses the central question: To what extent can coercive diplomacy be considered an effective and responsible instrument of statecraft today, given its profound risks and the evolving strategic landscape? The analysis proceeds in two parts. Part I evaluates the foundational elements influencing coercive diplomacy’s success or failure. It finds that effectiveness is highly conditional, hinging on elusive factors like demonstrable credibility, perceived legitimacy (often enhanced by multilateral support), and conducive context. Simultaneously, it highlights the significant inherent risks of unintended escalation, counter-productive radicalization, and regional destabilization, alongside the constraining force of ethical dilemmas and international legal norms regarding proportionality and legitimacy. Part II shifts to application and future perspectives. Examination of key historical case studies (Iraq, Iran, Cuba) reveals a spectrum of outcomes, from perceived success under extreme duress to costly failures, underscoring the strategy’s unpredictability. The analysis then confronts critical modern challenges: the sophisticated evolution of economic coercion beyond traditional sanctions, the ambiguity and escalatory potential of the cyber domain as a coercive instrument, and the disruptive influence of non-state actors complicating traditional state-centric models. The article concludes that the effectiveness of coercive diplomacy in the 21st century is highly questionable and its viability as a reliable tool is significantly diminished by both inherent risks and modern complexities. It should be viewed not as a default policy option but as a high-risk instrument of last resort. This study contributes by systematically integrating these factors, urging policymakers towards greater caution and emphasizing the need to prioritize conflict prevention, robust crisis management, multilateral cooperation, and integrated statecraft grounded in international law. Keywords: Coercive diplomacy, Crisis management, Escalation, International law